Model and Characterization of a Passive Biomimetic Ankle for Lower Extremity Powered Exoskeleton - Fournier, Brandon (Université d'Ottawa / University of Ottawa, 2018)
Lower extremity powered exoskeletons (LEPE) allow people with spinal cord injury (SCI) to perform activities of daily living, such as standing, walking, or stair and ramp ascent/descent. However, current LEPE walk slowly and require extensive use of forearm crutches to maintain user stability. Consequently, this limits LEPE time of use and overall system performance. While the biological ankle is known to be critical for energy efficiency, speed, and stability in able-bodied walking, current LEPE do not include biomimetic ankle designs and thus limit device performance. The objective of this thesis is to determine biomimetic ankle mechanics for a LEPE, thereby defining ankle design requirements that could reduce crutch loads and thus extend LEPE use. Virtual prototyping techniques were used to achieve this objective. Two 3D models of a real LEPE (ARKE, Bionik Laboratories) attached to a human musculoskeletal model were developed and validated. The first model (biomimetic model) was driven by 3D marker kinematics from 30 able-bodied participants walking at four realistically slow LEPE walking speeds. The second model (SCI model) was driven by 3D marker kinematics from five SCI participants walking in the ARKE LEPE with instrumented forearm crutches. Once the models were validated by comparing predicted to measured ground reaction forces (GRF) and centre of pressure (COP) trajectories, biomimetic LEPE ankle design requirements were determined. Ankle range of motion, quasi-stiffness, work, peak moment, and peak power were compared between human and human+ARKE models, across four gait phases and four slow walking speeds. The major findings were: the human+ARKE model had significantly different quasi-stiffness values across all four gait phases; quasi-stiffness increased with increasing speed; the human+ARKE model’s ankle always absorbed net-work, even at the fastest walking speed; quadratic regression was significantly more accurate than linear regression for modelling ankle quasi-stiffness. These results suggested that passive variable stiffness ankles incorporating quadratic elastic spring elements could achieve biomimetic ankle functions and thus potentially increase LEPE user walking speed, stability, and reduce overuse of crutches.
Keywords: exoskeleton; ankle; simulation; biomechanics